Effective CMV prophylaxis with high‐dose valaciclovir in allogeneic hematopoietic stem‐cell recipients at a high risk of CMV infection. Issue 1 (1st December 2022) - Douglas, Genevieve; Yong, Michelle K.; Tio, Shio Yen; Chau, Maggie; Prabahran, Ashvind; Sasadeusz, Joe; Slavin, Monica; Ritchie, David; Chee, Lynette
Abstract: Background: Cytomegalovirus (CMV) infection increases mortality and morbidity following allogeneic hematopoietic stem‐cell transplantation (alloHSCT). Universal antiviral prophylaxis with letermovir is effective but unsubsidized in Australia. Valaciclovir demonstrates anti‐CMV activity in high doses, but few current real‐world studies explore its use as primary prophylaxis in high‐risk patients post‐alloHSCT. Methods: We performed a retrospective analysis of alloHSCT recipients at high risk of clinically significant CMV infection (cs‐CMVi), defined as a plasma CMV DNA viral load of >400 IU/ml requiring preemptive therapy, or CMV disease. High‐risk recipients were CMV seropositive and underwent T‐cell depleted, haploidentical or umbilical cord stem‐cell transplants. Consecutive patients transplanted from July 2018 to January 2020, treated with valaciclovir 2 g TDS from day +7 to +100 (HD‐VALA), were compared to a historical cohort (July 2017–June 2018) who only received preemptive CMV therapy, and standard valaciclovir (SD‐VALA) for varicella/herpes prophylaxis. We compared incidence of and time to cs‐CMVi. Results: In the SD‐VALA cohort ( n  = 27, median CMV follow‐up duration 259 days), 23/27 (85%) developed cs‐CMVi at a median of 39 days. For the HD‐VALA cohort ( n  = 35, median CMV follow‐up duration 216 days), 19/35 (54%) developed cs‐CMVi, at a median of 68 days. Time to cs‐CMVi was significantly longer in HD‐VALA cohort ( p  < .0001). On multivariate analysis, HD VALA reduced the risk of cs‐CMVi (HR 0.32, p  = .0005). Conclusions: In alloHSCT recipients at high risk for cs‐CMVi, HD‐VALA resulted in lower cumulative reactivation, and delayed reactivation, reducing requirement for preemptive CMV therapy in the early post‐engraftment period. Abstract :